International Competitiveness of Asian Firms: An Analytical Framework - Rajiv Kumar; Doren Chadee (Asian Development Bank (ADB), 2002)
"Following the Asian financial crisis of 1997-1998, recovery in the export sector of crisis-affected countries has been slow, thereby raising important questions on the international competitiveness of firms in this region. In order for policymakers to restore the dynamism of Asian firms and ensure sustained export growth in the long term, it is instructive to, first, identify the sources of competitiveness of enterprises in this region. This paper, which provides the theoretical framework to RETA 5875, develops a conceptual model to explain the determinants of international competitiveness of Asian firms and offers research propositions. The model posits that international competitiveness is affected by the firm's human resource orientation, extent of technological innovation, organizational structure, government industrial policy, access to capital, as well as state of the financial market."
hdl:11540/1922
Keywords: 330